Patient Satisfaction Reviewed from Dimension Reliability in Community Health Center - Herbert Wau; Dewinta Isabora Gustrianingsih Purba (Universitas Muhammadiyah Yogyakarta, 2019)
Patient satisfaction in health care is a key indicator of the success of health service delivery. Reliability is the ability to provide the promised service immediately, accurately and satisfactorily. If the reliability dimension is not implemented properly it will cause problems so that it can affect patient satisfaction. The purpose of this study was to determine the effect of the reliability dimension on patient satisfaction at the Padang Bulan Community Health Center in Medan. Data collection was carried out by in-depth interviews (in-depth interviews). Data analysis was performed descriptively and presented in narrative form. The sample in this study were 4 patients and 2 health workers with a total of 6 people. The results showed that there was an influence on the speed of health checks, accuracy of service schedules, and health workers provided clear information on patient satisfaction at the Padang Bulan Community Health Center in Medan.